Evolution of the internal load and physical condition of wheelchair basketball players during the competitive season - Romarate, Ander; Yanci, Javier; Iturricastillo, Aitor (Frontiers in Physiology, 2023)
The objectives of this study were to describe differentiated perceived training and match load (dRPE-L) and players’ physical condition changes during a wheelchair basketball (WB) full season and to analyze the association between dRPE-L and changes in physical condition during the season. Nineteen Spanish Second Division WB players participated in this study. For a full season (10 months, 26 weeks), dRPE-L was assessed with the session-RPE method, separating respiratory (RPEres-L) and muscular (RPEmus-L) perceived load. The physical condition of the players was also assessed at four different times during the season (T1, T2, T3 and T4). The results showed a significantly higher total and average accumulated muscular RPE load (RPEmusTOT-L and RPEmusAVG-L) than total and average respiratory load (RPEresTOT-L and RPEresAVG-L) (p<0.01; ES=0.52 to 0.55). No significant changes were observed in the physical condition of the players at the different moments of the season (T1vs.T4). Moreover, a significant association was observed only between RPEresTOT-L and one variable of Repeated Sprint Ability (RSA) (r=0.90, p<0.05). The results suggest that the competitive season represented considerable neuromuscular involvement in these players.